Realitas Pengaruh Penggunaan Teknologi Augmented Reality dalam Pembelajaran terhadap Pemahaman Konsep Siswa - Hermawan, Agus; Hadi, Saptono (Jurnal Simki Pedagogia, 2024)
Augmented Reality (AR) technology provides great capabilities in improving the quality of learning, but its implementation still faces challenges. This SLR research seeks to explore the real implementation of AR learning media application designs in classroom teaching as a driver of student understanding of concepts. Using the literature review method, the research analyzed 10 related journals. Results show AR enhances students' interactive experiences, concept visualization, and learning interest. The implications include curriculum development and innovative learning methods, as well as diverse AR application opportunities. Follow-up includes learning needs, developing instructional design-based applications, providing infrastructure, training educators, and regular evaluations. Research confirms that Augmented Reality technology has multi-functions, especially 3-dimensional spatial design has great potential in improving the quality of teaching in the classroom.